An Empirical Critique of On-Demand Routing Protocols against Rushing Attack in MANET - S. Ashok Kumar; E. Suresh Babu; C. Nagaraju; A. Peda Gopi (Institute of Advanced Engineering and Science, 2015)
Over the last decade, researchers had proposed numerous mobile ad hoc routing protocols for which are operate in an on-demand way, as standard on-demand routing protocols such as AODV, DSR and TORA, etc., have been shown to often have faster reaction time and lower overhead than proactive protocols. However, the openness of the routing environment and the absence of centralized system and infrastructure make them exposed to security attacks in large extent. In particular, one such kind of attacks is rushing attack, which is mostly hard to detect due to their inherited properties, that alters the network statistics radically. In this paper, we modeled a rushing attack which is a powerful attack that exploits the weaknesses of the secure routing protocols. Moreover, to know the weakness and strength of these protocols, it is necessary to test their performance in hostile environments. Subsequently, the performance is measured with the various metrics, some ot them are average throughput, packet delivery ratio, average end-to-end delay and etc., to compare and evaluate their performance.